Early and delayed Laparoscopic Cholecystectomy of Acute Cholecystitis in Department of Surgery, Faculty of Medicine, University of Misurata at period between 2018-2021 (Journal of Academic Research, 2025)
Background: Early laparoscopic cholecystectomy has been approved as the treatment of choice for acute cholecystitis because of shorter hospital stay and no increased morbidity when compared to delayed cholecystectomy, That's why Many surgeons prefer to do early laparoscopic cholecystectomy (within 3 days from starting symptoms) for treatment of acute cholecystitis. Her in my study we will compare between early (within 72hr) and elective(after 72hr) laparoscopic cholecystectomy of acute cholecystitis in all age group (young, adult, or elderly patients).Methods: Laparoscopic cholecystectomy was performed within 72 hours of symptoms in 84 patients (group 1) and after 72 hours in 116 patients (group 2).The result of our study reveal relatively no difference between two groups in postoperative analgesia requirements, the rate of conversion ,or postoperative complications. But in the group 1 (early LC) had longer operating time, and shorter hospital stay. Most studies published in international literature show a statistically significant difference in the total hospital stay.
Keywords: Laprascopic cholecystectomy; acute cholecytitis; delayed cholecystectomy